Impact of number of stems per stool on mechanical harvesting of a Eucalyptus globulus coppiced plantation in south-west Western Australia. Issue 2 (3rd April 2018) - Strandgard, Martin; Mitchell, Rick
Abstract : Coppice regeneration of eucalypt plantations is increasingly being used in Australia to reduce re-establishment costs. However, little is known about the impact of early coppice reduction regimes on harvester performance during clearfelling. The trial compared the productivity, time consumption, cost and fuel use of a single-grip harvester (Hyundai 210LC-9 base and SP 591LX harvesting head) clearfelling a 10.5-year-old, second-rotation coppiced Eucalyptus globulus stand in south-west Western Australia for chip logs. Coppice stems had been reduced to one stem or two stems per stool or left untreated. Time and piece counts were used to determine harvester productivity. Harvester cycle and elemental times and the number of logs and harvester head passes per stem were obtained from video recordings. Harvester fuel use was determined by refilling the fuel tank to the same point each day. Stem size was the major factor influencing harvester productivity (20.8 m3 per productive machine hour without delays [PMH0 ], 11.8 m 3 PMH0 −1 and 8.6 m 3 PMH0 −1 in the single-stem (mean stem volume [MSV] 0.21 m 3 ), two-stem (MSV 0.09 m 3 ) and untreated trial areas (MSV 0.06 m 3 ), respectively. Estimated harvester cost (AU$ m –3 ) was considerably greater for the two-stem and untreated trial areas, which reflected the lower harvester productivity in these areas. Processing time represented over 60% of the total cycle time for all trial areas. Coppice characteristics resulted in significantly different moving/positioning times between trial areas. However, this difference had no impact on cycle times. Number of logs per stem was a significant variable in cycle and processing time regressions for all trial areas and felling time for the single-stem trial area. Number of harvester head passes was a significant variable in cycle and processing time regressions for the single-stem trial area and processing times for the two-stem trial area, although its effect was less than that of the number of logs per stem. Fuel consumption (L PMH0 −1 ) was relatively constant between the trial areas, hence harvester energy intensity (L m −3 ) reflected the harvester productivity in each trial area.